'You need to be healthy to be sick': exploring older people's experiences with medication packaging at home. (8th March 2022) - Carli Lorenzini, Giana; Bell, Alison; Olsson, Annika
Abstract: Background: the ageing global population is living longer with complex health conditions addressed by multiple medications. Little is known about how older people manage these medications and associated packaging at home. Objectives: to explore how older people manage the use of multiple medication and associated packaging in their process of self-care. Methods: fifteen older, home-dwelling participants (mean age = 76.2 years) participated in this study. All participants used three or more daily medications and resided in Southern Sweden. Data were collected using photographs and written diaries completed by each participant over seven consecutive days, complemented by researcher-led interviews. Interviews and diary data were analysed using thematic analysis. Results: six major themes emerged and are discussed: systematic organisation of medication, design of medication packaging, design of tablets, ease of package opening, emotional response to the need for medication, and environmental waste. Conclusion: packaging plays an important role in protecting products and enabling easy storage, product longevity and transportation. Medication packaging is no exception. However, the design of medication packaging poses challenges for older people managing medications for their chronic health conditions at home. There is a need to facilitate the systematic management of multiple medications, especially for new medication regimes or changes in treatment. Design of both packaging and medication should be consistent for older users to avoid potential errors; difficulties opening packaging can potentially hinder adherence to treatment. This study highlights the need for patient-centred solutions and involvement of older people in a co-design process for medication and packaging design.